2014
DOI: 10.1111/pme.12542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pain Reporting and Associated Health Outcomes Across Emerging Markets and Developed Countries

Abstract: Pain was associated with burden across all study outcomes in all regions. Yet, differences emerged in the degree of impairment, pain reporting, diagnosis, treatment rates, and characteristics of patients between emerging and developed nations, thus helping guide a broader understanding of this highly prevalent condition globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
7
26
4
1
Order By: Relevance
“…Our findings on the reporting of pain/discomfort coincide with those of earlier multi-country studies that showed a tendency towards lower rates or intensity of self-reported pain in Japan than in other countries [7, 8, 27]. Despite lower rates of self-reported pain/discomfort in Japan, we found that this was the most important dimension in explaining respondents’ self-reported EQ-5D-3L VAS scores.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings on the reporting of pain/discomfort coincide with those of earlier multi-country studies that showed a tendency towards lower rates or intensity of self-reported pain in Japan than in other countries [7, 8, 27]. Despite lower rates of self-reported pain/discomfort in Japan, we found that this was the most important dimension in explaining respondents’ self-reported EQ-5D-3L VAS scores.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to pain reporting, there is evidence that this can vary quite widely across countries; for example, the results of a survey published in 2014 showed that pain reporting and treatment rates were lower in China (6.2% and 28.3%, respectively) and Japan (4.4% and 26.3%, respectively) than in the other countries involved (≥14.3% and 35.8%, respectively) [7]. Substantial variations between countries in the rate of pain reporting have also been reported in primary care [8] and among patients with cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, among Japanese physicians who had previously treated fibromyalgia patients, less than half (44.2%) self-reported wanting to accept more patients with this chronic pain condition 35. Furthermore, cross-national data showed that Japan had the lowest rate of pain reported (4.4%) and treated (26.3%), compared to other developed countries, including the USA (23.8% experienced pain and 40.1% treated) and Europe (including the UK, France, Germany, Italy, and Spain; 20.2% experienced pain and 47.0% treated) 36. Therefore, underdiagnosis and low acceptance of patients with fibromyalgia by physicians coupled with low pain reporting among patients may hinder the ability of Japanese patients to obtain a diagnosis and receive treatment for fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involve inflammatory responses, peripheral and central sensitization, neuronal plasticity changes, and activation of spinal gliacytes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%